IMPLIKASI KEBIJAKAN RUANG TERBUKA HIJAU DALAM PENATAAN RUANG DI JAWA BARAT - nadia astriani (Universitas Lampung, 2014)
Green Open Space (RTH) diminishing lead to the emergence of insecurity and social diseases and influence the improvement of micro-climate, air pollution, floods, and various other negative environmental impacts. The study was conducted by looking at the green open space in a holistic manner. This method is expected to explain the policy of the green space in West Java and the policy implications of the Spatial Plan. Research results indicate the overall amount of green space in West Java has not fulfilled the amount of 30% as mandated by the Law on Spatial Planning, so the RTH policy directed at meeting the quota of 30%, with a range of strategies for improving the quality and quantity of green space Regency/City. RTH is an important part of City Spatial System, the procurement of green space is part of planning in the protection and management of the environment. As part of the layout, RTH is an instrument of prevention of pollution and/or damage to the environment. Keywords: Policy, Green Open Space, Spatial